Design and development of neutral-point clamped (NPC) inverter - Shan, Yuqing (Nanyang Technological University, 2020)
Nowadays, the application of renewable energy sources is emerging in generating electricity in response to the energy shortage and environmental protection. Therefore, the design and development of the energy conversion system is crucial for the integration of the renewable energy into the power grid. For the energy conversion system, the multi-level inverter is widely employed with regard to its high power, low voltage stress on switching devices and reduced harmonics distortion. Among various inverters, the three-level neutral-point-clamped (NPC) inverter is mostly used in industrial field. In this thesis, the design for the main circuit and the development of the control scheme in the NPC inverter are illustrated. In addition, this thesis proposes the method of designing a proper LC filter to reduce the harmonics and regulate the waveform of the output voltage and current. After that, switching power losses and conduction power losses of a switching device in the NPC inverter are estimated and compared to that in the T-type inverter, aiming to describe the advantages and disadvantages of the two inverters.